Mapping the quality of Norwegian health information –Does it facilitate informed choices? - Jürgen Kasper; Betül Cokluk; Marianne Molin; Anke Steckelberg; Sandro Zacher; Victoria T. Hjellset (PLoS ONE, 2026)
Background and aim Health literacy refers to the ability to use relevant information to make informed choices. However, the quality of the available information influences how well individuals can make those choices. Evidence-based recommendations for the development and design of health information have recently been published. In this study, we aimed to map the quality of Norwegian web-based health information across selected public health domains. Methods Using a multiple-cross-sectional design, we assessed information in 16 health domains relevant to infants, children, and youth. Convenience samples were drawn using structured Google searches. Three independent raters conducted the quality appraisal by applying the 19 criteria of the Mapping the quality of health information checklist. Inter-rater reliability was calculated using T-coefficients. Information quality was statistically described. To explain variance in quality, mean quality scores were compared across three independent variables: the type of the health problem, target group, and provider class. Results Across the surveys, 1,948 health information materials from 64 subdomains were assessed. Inter-rater reliability was excellent (mean T = .89/.90). On average, the materials complied with 22% (range: 0–73%, standard deviation = .09) of the current minimal standard. Differences between types of problems or target groups were marginal. No differences were found between information provided by health authorities, health services, or commercial entities. Conclusion Norwegian web-based health information is not of sufficient quality to facilitate informed health choices made by citizens. These findings apply across a wide range of public health domains relating to infants, children, and youth. In the absence of appropriate health information of acceptable quality, estimates of the public’s level of health literacy may need reconsideration. Further research is needed to appraise the quality of information in other health domains and countries.